2021
DOI: 10.1177/19375867211016342
|View full text |Cite
|
Sign up to set email alerts
|

Aging-in-Place: Residents’ Attitudes and Floor Plan Potential in Apartment Buildings From 1990 to 2015

Abstract: Objectives: We investigated apartment designs in apartment blocks built 1990–2015 in Gothenburg, Sweden. We investigated the residents’ attitudes toward their previous, present, and future housing and their perceived possibilities for aging-in-place. We analyzed their apartments, focusing on the possibilities for aging-in-place in future care situations concerning bedroom capacity in a care situation; spatial proximity between bathroom, bedroom, storage, and entrance; and functional autonomy in a care situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Previuos Swedish studies have focused on the design of apartments that can support aging-in-place [12] and the functionality of municipal support to create good conditions for this group [13]. International studies have draws attention to challenges regarding cost-efficient renovation measures that will benefit an aging population [14], but no similar study is found in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Previuos Swedish studies have focused on the design of apartments that can support aging-in-place [12] and the functionality of municipal support to create good conditions for this group [13]. International studies have draws attention to challenges regarding cost-efficient renovation measures that will benefit an aging population [14], but no similar study is found in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing to reside in one's longtime residence has implications far beyond the mere provision of housing per se (Wiles et al, 2011). In a study conducted in Sweden, Andersson et al (2021) concluded that small apartments for independent living are most preferred as they allow for personalized adaptation-if they are internally well-planned from the outset. In a related study, accessory dwelling units proved a valuable addition to housing options for older persons (Maaoui, 2018).…”
Section: Comparative Assessment Of Facility Design Featuresmentioning
confidence: 99%